The Role of Genomics and Transcriptomics in Characterizing and Predicting Patient Response to Treatment in Triple Negative Breast Cancer (TNBC) - Franklin Eduardo Corea-Dilbert; Muhammad Zubair Afzal (Onco, 2025)
Breast cancer is a complex disease that is one of the leading causes of cancer-related mortality in women worldwide. Of the subtypes of breast cancer, the most aggressive subtype is triple negative breast cancer (TNBC) due to its lack of targets that could be leveraged for treatment in other subtypes. Current treatment options for both local and metastatic TNBC include radiation therapy, chemotherapy, surgery, targeted therapy, and immunotherapy, which has been gaining popularity in recent years. The role of targeted therapy in TNBC is somewhat limited due to the paucity of therapeutic personalized targets, and, due to the heterogeneity of the disease, the effectiveness of these different modalities varies from patient to patient. These unique elements are the foundation of personalized medicine where genomics and transcriptomics play a critical role in increasing granularity in patients’ disease and treatment. The purpose of these molecular tools is to identify biomarkers that could be used to further characterize each patient’s unique disease features and to predict how certain treatment modalities will affect patient survival and prognosis. The interplay between these biomarkers and molecular pathways involved in treatment response with disease progression and aggressiveness is a complex phenomenon. In this review, we describe the current state of the literature in regard to biomarkers that show promise in the clinical setting to predict response to treatments such as chemotherapy, radiation, and surgery in locally advanced and metastatic TNBC.